2014
DOI: 10.4028/www.scientific.net/msf.804.297
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chromium Content and Impact Load on Microstructures and Properties of High Manganese Steel

Abstract: In this paper, the effects of Cr content and impact load on the microstructure and properties of High Manganese Steel (HMS) were investigated. The results show that the hardness of HMS was increasing when the Cr content increased, but the hardness was not much changing when the Cr contents changed from 2% to 2,5% of weight. Under the impact load, the microstructure and the hardness were changed also. The Cr content effected on the depth of transition layer on surface under the impact load and the twinning occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 3 publications
1
3
0
Order By: Relevance
“…Specifically, the reductions in hardness values were 26, 28, and 26 for Steels 1, 2, and 3, respectively, which were not significantly different. This behavior was also observed by Khanh et al [26] in high-manganese steel, wherein hardness did not change much when the chromium content increased from 2% to 2.5%. Interestingly, Steel 3, which had no chromium content, showed a change in hardness even when varying chromium in the range [0.13, 0.656] wt%, suggesting that the chromium content in that composition of metals had no effect on hardness.…”
Section: Analysis Of the Impact Of Chromium Content On The Hardness O...supporting
confidence: 83%
See 1 more Smart Citation
“…Specifically, the reductions in hardness values were 26, 28, and 26 for Steels 1, 2, and 3, respectively, which were not significantly different. This behavior was also observed by Khanh et al [26] in high-manganese steel, wherein hardness did not change much when the chromium content increased from 2% to 2.5%. Interestingly, Steel 3, which had no chromium content, showed a change in hardness even when varying chromium in the range [0.13, 0.656] wt%, suggesting that the chromium content in that composition of metals had no effect on hardness.…”
Section: Analysis Of the Impact Of Chromium Content On The Hardness O...supporting
confidence: 83%
“…Our findings are in good agreement with the trends reported in the literature. For example, Khanh et al [26] found that the hardness of high-manganese steel increased when the chromium content increased, but the hardness did not change much when the Cr content changed from 2% to 2.5% of the weight. Chromium tends to increase hardness penetration.…”
Section: Analysis Of Other Alloying Elementsmentioning
confidence: 99%
“…After passing through an instantanous cooling process, they produce polycrystalline crystals instead of single crystals and under such conditions, several austenitic ions bind together and prevent crystallization of the crystals. Thus, they promote the same crystal growth and smooth the structure [16,17]. The steel is alloyed by alloy elements as: Cr; V... M7C3 crystals size is larger than crystalline raddie than crystalline radii, reducing the length.…”
Section: Introductionmentioning
confidence: 99%
“…High manganese steel (HMS) exhibits both excellent toughness and hardenability under high impact conditions [1,2]. Hence, it has been widely used in specific applications such as rail tracks, dredge buckets, hammer crushers and a variety of high impact and wear-resistance operations [3][4][5]. Among various ceramic particles, titanium carbide-TiC is expected to combine with HMS to enhance the hardness and the wear-resistance of HMS.…”
Section: Introductionmentioning
confidence: 99%